Cervical vertebral maturation as a predictor of the adolescent growth spurt - Grave Keith; Townsend Grant (Sciendo, 2003)
The aim of this study was to investigate the application of an improved version of the Cervical Vertebral Maturation (CVM) method in a group of indigenous Australians and to relate the ossification events to the timing of peak growth in both stature and the mandible. Data were obtained from longitudinal records of 74 Australian Aboriginal children living at Yuendumu Settlement in the Northern Territory of Australia. CVM stages were limited to particular growth periods: in a large percentage of subjects stage 1 occurred in the pre-peak period of growth, stages 2 and 3 in the peak period, and stages 4 and 5 in the post-peak period. Our findings were similar to those reported in other ethnic groups, suggesting that they can be applied more generally in orthodontic practice to assess a child's growth activity. In the majority of boys, CVM stage 2 would appear to be a good time to commence an orthopaedic phase of treatment, whereas in girls, results would support an earlier more cautious approach, sometime before stage 2 is reached. Peak growth occurs between stages 2 and 3 and timing is extremely important to maximize the effects of growth in the treatment process.